Involvement in sustainable tourism development in Bandar Hilir, Melaka / Siti Rohani Ahmad Suhaimi , Nur Fakhira Mohd Rosli and Nadia Anis Mohd Azmee - Ahmad Suhaimi, Siti Rohani; Mohd Rosli, Nur Fakhira; Mohd Azmee, Nadia Anis (Faculty of Hotel and Tourism Management, 2014)
Community is one of the important elements in tourism especially in sustainable tourism development. Both community and tourism sector can get benefits from community involvement in sustainable tourism development. Thus, the development of sustainable tourism is hard to achieve without the support from the community residents because it is one of the important factor for ongoing community development. The main objectives of this study are to measure the level of community involvement and to examine the effectiveness of current practice in encouraging community involvement in sustainable tourism development in Bandar Hilir Melaka. Consequently, to achieve the purpose of the research, we distributed the questionnaire among local community around Bandar Hilir, Melaka. This investigation will give more understanding about the ways and the level of community involvement in sustainable tourism development especially for government sector, and any responsible person that related with sustainable tourism development in Bandar Hilir, Melaka. The result show that community slightly involve in sustainable tourism development based on the measuring level of community involvement and to examine the effectiveness of current practice in encouraging community involvement in sustainable tourism development in Bandar Hilir Melaka.